Pemanfaatan Limbah Bungkil Sawit Sebagai Pakan Ikan Alternatif - Lintang Rizkyta Ananda; Reno Susanto; Alfikri Gunawan; Yonada Setya Octamara; Said Zulamraini; Mohammad Ghimnastiar Ulsak; Alissya Rafiani (Sekolah Tinggi Ilmu Ekonomi Pariwisata Indonesia Semarang, 2024)
Catfish farming is a new livelihood being developed by the people of Lubuk Bendahara Timur village, Rokan Hulu district, Riau province. However, this effort faces challenges in terms of the use of expensive factory pellets, which account for about 60-70% of the total production cost. To overcome this problem, an alternative solution is proposed by producing fish pellets independently by utilizing palm oil waste in the village. Through this community service program, appropriate technology transfer was carried out for Lubuk Bendahara Timur villagers by empowering the local community in producing fish pellets independently. The implication of this program is the increased knowledge in optimizing the utilization of palm oil waste for fish pellet production, so as to reduce production costs, increase income, and manage waste effectively.